Antioxidant effects of methionine, ?-lipoic acid, N-acetylcysteine and homocysteine on lead-induced oxidative stress to erythrocytes in rats - Caylak, Emrah; Aytekin, Metin; Halifeoglu, Ihsan (Elsevier Gmbh, Urban & Fischer Verlag, 2008)
Lead, widely used in industry, is a great environmental health problem. Many studies have examined its effects on the health of both humans and animals. Experimental studies have shown that sulphur-containing antioxidants have beneficial effects against the detrimental properties of lead. The present study was designed to investigate markers of oxidative stress (hemoglobin (Hb) in whole blood, malondialdehyde (MDA) in sera; superoxidase dismutase (SOD) and glutathione peroxidise (GSH-Px) in erythrocyte hemolysate and vitamins A and E in plasma) in rats given lead (2000ppm) with or without sulphur-containing antioxidants (L-methionine (Met) (100 mg/kg/day), N-acetylcysteine (NAC) (800 mg/kg/day), L-homocysteine (Hey) (25 mg/kg/day), lipoic acid (LA) (50 mg/kg/day)) in their water for 5 weeks. In the lead group, Hb and plasma vitamin E levels were significantly lower whereas MDA levels were significantly higher compared to controls (p<0.05). Hb levels in lead-methionine and lead-LA groups were significantly higher than the lead group (p<0.01). MDA levels were reduced in all groups compared to the lead group (p<0.01). There was a decrease below control values in erythrocyte SOD (p<0.01) and GSH-Px (p<0.05) levels in the lead-LA group. Plasma vitamin A levels were significantly high in lead-methionine group compared to lead group (p<0.01). In conclusion, the data suggests that oxidative stress induced by lead is reduced by sulphur-containing compounds. (C) 2008 Elsevier GmbH. All rights reserved.
Keywords: lead; oxidative stress; methionine; lipoic acid; N-acetylcysteine; homocysteine